The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1042/bj20111234
|View full text |Cite
|
Sign up to set email alerts
|

Homo- and hetero-dimeric architecture of the human liver Na+-dependent taurocholate co-transporting protein

Abstract: The NTCP (Na⁺-taurocholate co-transporting protein)/SLC10A [solute carrier family 10 (Nav/bile acid co-transporter family)] 1 is tightly controlled to ensure hepatic bile salt uptake while preventing toxic bile salt accumulation. Many transport proteins require oligomerization for their activity and regulation. This is not yet established for bile salt transporters. The present study was conducted to elucidate the oligomeric state of NTCP. Chemical cross-linking revealed the presence of NTCP dimers in rat live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 40 publications
(53 reference statements)
6
51
0
1
Order By: Relevance
“…The central role of NTCP in hepatic uptake of conjugated bile acids was recently demonstrated using NTCP knockout mice, which also lost hepatic binding of the HBV preS1 domain (Slijepcevic et al 2015). Crosslinking and biochemical studies indicate that NTCP may exist as a dimer (Bijsmans et al 2012), although this hypothesis requires further verification. NTCP is complex glycosylated with four potential N-glycosylation sites, two of which (N5 and N11) have been confirmed (Hallen et al 2002).…”
Section: Expression and Physiological Function Of Ntcpmentioning
confidence: 95%
“…The central role of NTCP in hepatic uptake of conjugated bile acids was recently demonstrated using NTCP knockout mice, which also lost hepatic binding of the HBV preS1 domain (Slijepcevic et al 2015). Crosslinking and biochemical studies indicate that NTCP may exist as a dimer (Bijsmans et al 2012), although this hypothesis requires further verification. NTCP is complex glycosylated with four potential N-glycosylation sites, two of which (N5 and N11) have been confirmed (Hallen et al 2002).…”
Section: Expression and Physiological Function Of Ntcpmentioning
confidence: 95%
“…Furthermore, there is the potential for protein-protein interactions that could influence transporter function, similar to what has been shown for drug-metabolizing enzymes [18]. It has been demonstrated that some rat transporters expressed in hepatocytes, including NTCP [19] and OCT1, can form homo-oligomers [20]. In addition, a recent study showed that human OATP1B1 may form and function as oligomers [21].…”
Section: Introductionmentioning
confidence: 97%
“…Although homology analysis has shown that SLC10A4 belongs to the family sodium-bile acid cotransporters, experiments in rat and human cells either failed to confirm transport activity for bile acids or related molecules (Splinter et al, 2006; Geyer et al, 2008), or reported only low bile-acid transport activity for SLC10A4 (Bijsmans et al, 2012; Abe et al, 2013). The first evidence for a function of SLC10A4 in the brain was reported from the Kullander group (Zelano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%